132k views
4 votes
Simplify the expression. Write the answer using scientific notation. (5*10^7)(6*10^4)

User Mike Wise
by
4.9k points

2 Answers

4 votes

Answer:


3 * {10}^(12)

Explanation:


\: \: \: \: \: (5 * {10}^(7) )(6 * {10}^(4) ) \\ = 5 * 6 * {10}^(7) * {10}^(4) \\ = 30 * {10}^(7 + 4) \\ = 3 * 10 * {10}^(11) = 3 * {10}^(12)

User Byrd
by
4.7k points
2 votes

Answer:

30 x 10^11

Explanation:

See attachment below

Simplify the expression. Write the answer using scientific notation. (5*10^7)(6*10^4)-example-1
User Ons Ali
by
4.8k points